Exploring Malaysian Traditional Postpartum Care Practices ‎Among Practitioners - Adnan, Adni Halianie; Hasbollah, Hasif Rafidee; Mukhtar, Dzulkifli; Azmi, Adlina (International Journal of Basic and Applied Sciences, 2025)
This study explores traditional postpartum care practices among practitioners in Malaysia, focusing on techniques, dietary practices, and the ‎role of education and certification in ensuring effective care. It aims to understand how these practices, deeply rooted in cultural and ‎historical beliefs, contribute to maternal recovery during the postnatal period. The findings reveal that traditional practices, including hot ‎stone compression, postpartum massage, body wrapping, vaginal steam baths, and herbal remedies, are widely utilized to promote healing ‎and restore physical and mental health after childbirth. Dietary practices align with traditional beliefs emphasizing "hot" foods for recovery ‎and modern approaches focusing on balanced nutrition. Practitioners’ knowledge, often inherited or formally trained, plays a critical role in ‎maintaining the efficacy and safety of these methods. Certifications such as SKM and DKM ensure professionalism, while modern ‎adaptations like saunas offer safer alternatives to certain traditional techniques. Traditional postpartum care practices in Malaysia ‎significantly aid maternal recovery by integrating cultural wisdom and modern healthcare standards. While these methods remain vital for ‎physical and emotional well-being, further emphasis on formal training and safety enhancements can help sustain their relevance in ‎contemporary healthcare settings. This research discovers traditional postpartum care practices, dietary intake during postpartum, and ‎education and information among practitioners in Klang Valley‎.